THE EFFECT OF THE BAMBOO DANCE COOPERATIVE LEARNING MODEL ON IMPROVING STUDENTS' LEARNING OUTCOMES IN THE FIQIH SUBJECT FOR CLASS VIII AT MTS NURUL IHSAN NW TANJUNG LUAR - Sarina (Journal of Islamic Religious Studies, 2024)
This study aims to determine the effect of the bamboo dance cooperative learning model on improving students' learning outcomes in the Fiqih subject for class VIII at MTs Nurul Ihsan NW Tanjung Luar for the 2017/2018 academic year. This research was an experimental study. The population includes all class VIII students of MTs Nurul Ihsan NW Tanjung Luar, which consists of three classes, but only two classes were selected as samples. The sample was chosen using the cluster random sampling technique, where two classes were randomly selected and assigned, with class VIII-A as the experimental group and class VIII-C as the control group. The experimental group was taught using the bamboo dance cooperative learning model, while the control group used conventional methods. Students' pretest data were collected using a test method. The collected data were then analyzed using statistical techniques, specifically the t-test formula. Based on the data analysis, the calculated t-value was 6.959, while the t-table value at a 5% significance level with degrees of freedom (df) = 20+20-2 = 38 was 5.213. This indicates that the t-value is greater than the t-table value (6.959 > 5.213). Thus, it can be concluded that there is a significant effect of the bamboo dance cooperative learning model on improving students' learning outcomes in the FIQIH subject for class VIII at MTs Nurul Ihsan NW Tanjung Luar for the 2017/2018 academic year.